Probable Clostridium septicum pneumocephalus in a user of natural remedies with newly diagnosed diabetes mellitus type 1. (2019) - Mirzai, Saeid; Rifai, Ahmad Oussama; Webb, Shana; Rifai, Kareem; Reiner, Amanda
Abstract: Clostridium septicum encephalitis is a rare cause of spontaneous, non-traumatic pneumocephalus. Systemic infections with this organism have a fulminant course, likely leading to death within 48 hours, and are commonly associated with hematological or colonic malignancies. The effectiveness of an antibacterial regimen is unknown because of a lack of studies. The best prognosis is observed in patients undergoing early surgical intervention for localized intracranial processes. Here we describe a case of rapidly developing C. septicum sepsis as a result of bacteremia and hematogenous spread, resulting in encephalitis and pneumocephalus in a patient without a diagnosed malignancy. The patient presented to the emergency department with diabetic ketoacidosis, which led to the diagnosis of new-onset type 1 diabetes mellitus. There are currently 19 reported cases of C. septicum central nervous system infections in the literature, with 12 of them having pneumocephalus. Natural remedies, such as drinking kombucha tea and performing coffee enemas, that were used by our patient may have played a role in the dissemination of C. septicum . In survivors of this fulminant illness, colonic and hematologic malignancies should be excluded because of their association with such infections. Type 1 diabetes mellitus, drinking kombucha tea, and performing coffee enemas may be newly recognized risk factors associated with the dissemination of C. septicum .